Aboveground Biomass Along an Elevation Gradient in an Evergreen Andean–Amazonian Forest in Ecuador - Maza, Byron; Rodes-Blanco, Marina; Rojas, Edison (Frontiers in Forests and Global Change, 2022)
The aim of this research was to assess how aboveground biomass (AGB) changes along an altitudinal gradient in evergreen Andean–Amazonian forests [Evergreen Lower Montane Forest, northeastern Cordillera of the Andes; Evergreen Piedmont Forest (EPF), northeastern Cordillera of the Andes; and Evergreen Lowland Forest (ELF), Napo–Curaray] from 373 to 1,826 m above sea level (m.a.s.l.). All trees measured in nine permanent 0.36-ha plots (60 × 60 m) were ≥ 10-cm (diameter at breast height) in the aforementioned ecosystems. We assessed tree density, basal area, species richness, and AGB. In the tree inventory, we measured 2,132 trees (Lower Montane Forest 687, Piedmont Forest 773, and Lowland Forest 672). AGB (Mg ha–1) increases with decreasing elevations: 310.26 ± 81.59 (SD) for the Evergreen Lower Montane Forest, 347.73 ± 90.38 (SD) for the EPF, and 377.39 ± 42.73 (SD) for the ELF. Otoba glycycarpa and Alchornea latifolia were the species with the highest biomass importance value (BIV) in the Evergreen Lower Montane Forest (1,421–1,826 m.a.s.l.), Spirotheca rosea and Pouteria glomerata in the EPF (892–1,195 m.a.s.l.), and Otoba glycycarpa and Iriartea deltoidea in ELF (373–394 m.a.s.l.). Biomass contribution along the altitudinal gradient in the evergreen Andean–Amazonian forests is concentrated in few species. This has implications in forest management and reforestation programs where the main focus is on carbon sequestration.